Public Hearing of Draft Qanun District North Aceh on Management Old Oil Well: Publik Hearing Rancangan Qanun Kabupaten Aceh Utara Tentang Pengelolaan Sumur Minyak Tua - Jamaluddin; Elidar Sari; Malahayati; Arif Rahman; Marlia Sastro; Faisal Faisal; Yusrizal Yusrizal (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
North Aceh has many old Dutch heritage wells that still have the potential to be reactivated. Reactivation aims to regulate management so that there is a need for innovation to optimize the management of old wells whose innovation starts from the management concept to the technology used to make it more efficient, effective, and economical. This activity was carried out in the form of a public hearing on the draft Qanun of North Aceh Regency on the management of old oil wells involving the local government, DPRD, religious leaders, and community leaders. The public hearing results assessed that the management of old oil wells requires clear rules to avoid illegal drilling and tapping. Communities around the former drilling areas conduct mining in old oil wells, which are no longer economical for corporations. It is necessary to improve the legal basis that supports the establishment of a Draft Qanun on the management of old Dutch-owned oil wells in North Aceh District.